Pigments Production, Growth Kinetics, and Bioenergetic Patterns in Dunaliella tertiolecta (Chlorophyta) in Response to Different Culture Media - Yanara Alessandra Santana Moura; Daniela de Araújo Viana-Marques; Ana Lúcia Figueiredo Porto; Raquel Pedrosa Bezerra; Attilio Converti (Energies, 2020)
This work dealt with the study of growth parameters, pigments production, and bioenergetic aspects of the microalga Dunaliella tertiolecta in different culture media. For this purpose, cultures were carried out in Erlenmeyer flasks containing F/2 medium, Bold’s Basal medium, or an alternative medium made up of the same constituents of the Bold’s Basal medium dissolved in natural seawater instead of distilled water. D. tertiolecta reached the highest dry cell concentration (Xmax = 1223 mgDM·L−1), specific growth rate (µmax = 0.535 d−1), cell productivity (PX = 102 mgDM·L−1·d−1), and photosynthetic efficiency (PE = 14.54%) in the alternative medium, while the highest contents of carotenoids (52.0 mg·g−1) and chlorophyll (108.0 mg·g−1) in the biomass were obtained in Bold’s Basal medium. As for the bioenergetic parameters, the biomass yield on Gibbs energy dissipation was higher and comparable in both seawater-based media. However, the F/2 medium led to the highest values of moles of photons absorbed to produce 1 C-mol of biomass (nPh), total Gibbs energy absorbed by the photosynthesis (ΔGa) and released heat (Q), as well as the lowest cell concentration, thus proving to be the least suitable medium for D. tertiolecta growth. On the other hand, the highest values of molar development of O2 and consumption of H+ and H2O were obtained in the alternative medium, which also ensured the best kinetic parameters, thereby allowing for the best energy exploitation for cell growth. These results demonstrate that composition of culture medium for microalgae cultivation has different effects on pigments production, growth kinetics, and bioenergetics parameters, which should be taken into consideration for any use of biomass, including as raw material for biofuels production.